Pineapple Fruit Collapse: Newly Emerging Disease of Pineapple Fruit in Lampung, Indonesia - Joko Prasetyo; Titik Nur Aeny (Universitas Lampung, 2014)
ABSTRACTPineapple fruit collapse: newly emerging disease of pineapple fruit in Lampung, Indonesia Recently, a new disease on pineapple fruit has occurred in Lampung. Symptoms of the disease are complex. Fruits rotted and exuded copious liquid from the inter- fruitlet tissues accompanied by gas bubbles. Open spaces were formed inside the rotten fruit. Dissection of diseased fruit showed many cavities within its sceletal fibres and bad odour was exerted from the rotten tissues. A bacterial entity was isolated from the diseased materials. In a pathogenicity test, the isolated bacteria caused the same symptom as mentioned. In the growing-on test the crown of the heavily infected fruit showed heart rot symptom. Those indicated that the disease was pineapple fruit collapse. Both symptoms were known related to the same causal agent, Erwinia chrysanthemi (pineapple strain Dickeya sp.). In our opinion, this is the first report of pineapple fruit collapse in Indonesia.